Pengembangan Media Puppet Book Berbasis Pembelajaran Multiliterasi Pada Siswa Sekolah Dasar - Ayi Solihat; Nana Hendracipta; Rina Yuliana (Universitas Kanjuruhan Malang, 2020)
Abstract: Books as a medium of literacy are presented normally, making students less interested. Developing puppet media needs to be done. This research aims to develop Puppet Book media. This research method, R&D with Borg and Gall research design. The results of the study were in the form of a one-horned rhinoceros puppet learning media complete with books and audio attached to the puppets. The results of the validation of media experts (average value 90.285%), linguists (average value 99.167%), material experts (average value 92.105%). The results of validation (media, language, material) with a very decent category. The results of the questionnaire responses of students in field trials showed 96.41% with very good criteria. Based on these results, the final product in the form of a puppet book based on multiliteration learning is suitable for the learning activities of fourth grade elementary school students. Abstrak: Buku sebagai media literasi yang disajikan biasa, membuat peserta didik kurang tertarik. Pengembangkan media puppet perlu dilakukan. Penelitian ini bertujuan untuk mengembangkan media Puppet Book. Metode penelitian ini, R&D dengan desain penelitian Borg and Gall. Hasil penelitian berupa media pembelajaran puppet badak bercula satu yang dilengkapi buku serta audio yang terpasang pada puppet. Hasil validasi ahli media (nilai rata- rata 90,285%), ahli bahasa (nilai rata- rata 99,167%), ahli materi (nilai rata- rata 92,105%). Hasil validasi (media, bahasa, materi) dengan kategori sangat layak. Hasil angket respon siswa pada uji coba lapangan menunjukan 96,41% dengan kriteria sangat baik. Berdasarkan hasil tersebut, produk akhir berupa puppet book berbasis pembelajaran multiliterasi layak digunakan untuk kegiatan belajar siswa kelas IV SD.